Exploring EFL Students’ Speaking Challenges in Their Speaking for Social Purposes - Elisathusilawani, Elisathusilawani (Journal of English and Education (JEE), 2023)
Speaking is a crucial aspect when we learn English. However, speaking activities in class is a challenge for students from different educational backgrounds, such as those from remote areas in Bengkayang, West Kalimantan. This study aims to explore the speaking challenges of Bengkayang students in the Speaking for Social Purposes (SFSP) classes at the English Language Education Program, Universitas Kristen Satya Wacana (UKSW). To collect the data, this study used semi-structured interviews that involved seven students from Bengkayang who had taken SFSP classes. The data analysis indicated some challenges faced by the students, such as a lack of self-confidence, pronunciation errors, and lack of vocabulary. This research also hopes to provide practical tips and tricks for students in overcoming some English speaking difficulties in similar contexts. Recommendations for future research are also discussed. Keywords: EFL students, speaking for social purposes, speaking challenges